2007
DOI: 10.1179/joc.2007.19.4.423
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Pathological Characteristics and Response to Combination Therapy of Genotype 4 Chronic Hepatitis C Patients: Experience from a Spanish Center

Abstract: This observational study evaluated the characteristics of genotype 4 chronic hepatitis C (CHC) patients and their response to combination therapy in Spain. 383 patients with CHC, 44 with genotype 4-HCV infection, were investigated. Nineteen genotype 4-HCV infected patients received IFNalpha-2b (3 MU three times weekly) plus ribavirin (1-1.2 g/day) and ten received Peg-IFNalpha-2b (1.5 microg/kg/week) plus ribavirin (1-1.2 g/day) for 12 months. A sustained virological response (SVR) was evaluated. Genotype 4-HC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
12
1
3

Year Published

2008
2008
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 23 publications
1
12
1
3
Order By: Relevance
“…Another study (46) showed that treatment of patients with chronic HCV‐G4 by PEG‐IFN α‐2b and ribavirin induces a more rapid decrease in the HCV RNA level and a better SVR rate (62 vs. 13%) in Egyptians than in non‐Egyptians. In contrast, a Spanish study (47) evaluating the response of chronic HCV‐G4 treatment‐naive Spanish patients to combination therapy revealed a sustained virological response of 55%. Patients infected with HCV‐G4 showed a lower stage of fibrosis, lower viraemia and a higher SVR rate compared with genotype 1.…”
Section: Do All Patients With Chronic Hepatitis C Genotype 4 Achieve mentioning
confidence: 86%
“…Another study (46) showed that treatment of patients with chronic HCV‐G4 by PEG‐IFN α‐2b and ribavirin induces a more rapid decrease in the HCV RNA level and a better SVR rate (62 vs. 13%) in Egyptians than in non‐Egyptians. In contrast, a Spanish study (47) evaluating the response of chronic HCV‐G4 treatment‐naive Spanish patients to combination therapy revealed a sustained virological response of 55%. Patients infected with HCV‐G4 showed a lower stage of fibrosis, lower viraemia and a higher SVR rate compared with genotype 1.…”
Section: Do All Patients With Chronic Hepatitis C Genotype 4 Achieve mentioning
confidence: 86%
“…Another study (53) showed that treatment of patients with chronic HCV‐4 infection by PEG‐IFN‐α2b and ribavirin results in a more rapid decrease in HCV RNA level and a better SVR rate (62 vs. 13%) in Egyptians than in non‐Egyptians. In contrast, a Spanish study (54) evaluating the response of chronic HCV‐4 treatment‐naïve Spanish patients to combination therapy revealed a SVR of 55%. Patients infected with HCV‐4 had a lower stage of fibrosis, lower viraemia and a higher SVR rate compared with those with genotype 1.…”
Section: Pharmacogenetics Race Ethnicity and Personalized Medicine mentioning
confidence: 86%
“…Finally, the response to antiviral therapy may also differ significantly in this heterogeneous genotype. For instance, patients from Egypt and the Middle East showed significantly higher sustained virological response (SVR) rates when treated with peginterferon and ribavirin,14 15 compared to European patients treated with the same regimen 16 17. Again, the influence of insulin resistance shown to be a major predictor of SVR in other genotypes,18 19 20 21 is not determined in patients with HCV-4.…”
mentioning
confidence: 99%